A Thorough Analysis of the Opportunities and Challenges of Community Microgrid System Based on Renewable Energy in Bangladesh - Zaman, Md Rakibur; Sarker, Sudip; Halim, Md Abdul; Ibrahim, Salah; Haque, Abrarul (Control Systems and Optimization Letters, 2024)
The main objective of this extensive research is to assess the possible benefits and challenges related to the implementation of renewable energy-powered community microgrid systems in Bangladesh. Within the framework of Bangladesh's energy environment, the study aims to identify interesting possibilities present in such systems. Notable benefits include less reliance on traditional fossil fuels, increased accessibility to energy, and possible socioeconomic advantages for nearby populations. In addition, several issues that can prevent these microgrid systems from being deployed smoothly are carefully examined in this research. For sustained execution, these difficulties require a comprehensive and varied strategy since they involve technical complexities, economic concerns, regulatory obstacles, and social elements. Critical attention is paid to matters including community involvement, financial feasibility, regulatory frameworks, and the erratic nature of renewable energy sources. Furthermore, the research incorporates a comparative evaluation of current international community microgrid initiatives, deriving significant knowledge and lessons that are relevant to Bangladesh's particular circumstances. The study uses a comparative lens to attempt to provide useful and knowledgeable suggestions for stakeholders, energy practitioners, and policymakers who are involved in determining the future course of community microgrid projects in Bangladesh. When it comes to ecology, renewable energy sources like hydroelectric, solar, and wind power are far superior to fossil fuels. They decrease air and water pollution and emit the fewest greenhouse gases possible. Globally, there is an increasing interest in microgrid systems due to the pressing need to combat climate change, increase energy security, foster economic growth, and ensure that everyone has access to clean, dependable electricity. This paper offers a roadmap for the effective integration of community microgrid projects customized to Bangladesh's unique energy landscape, acting as a nuanced guide for strategic development.